PENGETAHUAN INVESTASI, MOTIVASI INVESTASI, LITERASI KEUANGAN DAN LINGKUNGAN KELUARGA PENGARUHNYA TERHADAP MINAT INVESTASI DI PASAR MODAL - Akhmad Darmawan; Kesih Kurnia; Sri Rejeki (P4M STIE Putra Bangsa, 2019)
This study aims to analyze the effect of investment knowledge, investment motivation, financial literacy and family environment on the interest in investing in the capital market. This type of research is quantitative. The population of this study were students of the Management Study Program of the Faculty of Economics and Business, Muhammadiyah Purwokerto University in the year 2016 and 2017 with the sample criteria of active students of FEB UMP and those who were / had taken financial management and entrepreneurship courses. Data collection in this study using the questionnaire method. Instrument testing was analyzed using validity test and reliability test. Data analysis techniques used in this study are classic assumptions and multiple linear regression analysis. The results showed that: (1) investment knowledge, investment motivation, and financial literacy simultaneously had a significant effect on investment interest. (2) investment knowledge partially does not affect investment interest. (3) investment motivation partially has a significant effect on investment interest. (4) financial literacy partially has a significant effect on investment interest. (5) the family environment partially has a significant effect on investment interest. keywords: Knowledge, Motivation, Literacy, Environment, Interests.